2013
DOI: 10.1016/j.jmbbm.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Deformationally dependent fluid transport properties of porcine coronary arteries based on location in the coronary vasculature

Abstract: Objective Understanding coronary artery mass transport allows researchers to better comprehend how drugs or proteins move through, and deposit into, the arterial wall. Characterizing how the convective component of transport changes based on arterial location could be useful to better understand how molecules distribute in different locations in the coronary vasculature. Methods and results We measured the mechanical properties and wall fluid flux transport properties of de-endothelialized (similar to post-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 53 publications
(91 reference statements)
0
33
0
Order By: Relevance
“…[1][2][3][4][5] We hypothesize that these failures would be minimized by evaluating in situ coronary artery drug delivery. [6][7][8][9][10][11][12][13][14] Restenosis was minimized by improving drug retention and transport in the coronary artery. Drug delivery to the tunica media has reduced or prevented migration and proliferation of vascular smooth muscle cells that cause restenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] We hypothesize that these failures would be minimized by evaluating in situ coronary artery drug delivery. [6][7][8][9][10][11][12][13][14] Restenosis was minimized by improving drug retention and transport in the coronary artery. Drug delivery to the tunica media has reduced or prevented migration and proliferation of vascular smooth muscle cells that cause restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by our findings that demonstrate drug transport and mechanical properties of the porcine coronary arteries vary as a function of vessel and location. [6][7][8] However, currently, there is no ideal imaging modality to monitor and quantify drug delivery to the coronary artery with sub-mm precision.…”
Section: Introductionmentioning
confidence: 99%
“…In order to build realistic and functional models the study of soft tissue microstructure has been an active research area. In particular, many studies aim to understand the extension and reorganization mechanisms of collagenous structures on different tissues such as tendons (Sasaki and Odajima, 1996;Screen et al, 2004), skin (Brown, 1973), connective tissue (Liao et al, 2005;Purslow et al, 1998), or arteries (Keyes et al, 2013;Rezakhaniha et al, 2012;Wang et al, 2013). Indeed, the changes in the microstructure at the fiber level can impact greatly the mechanical properties of the tissue and thus its functional purpose, affecting cell environment and behavior, leading to diseases or disorders (Engler et al, 2006;Koch et al, 2014;Pizzo et al, 2005;Robertson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the severity and frequency of coronary artery disease, the frequency of intervention, and the analysis of the coronary artery vasculature pre-and post-intervention are studied in vivo, ex vivo, in vitro, and in silico with high frequency [1][2][3][4][5][6][7][8][9][10][11][12]. One area of interest is transport through the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported variations in the measured fluid and mass transport properties of porcine coronary arteries based on arterial location [4,16]. One of these studies indicated differences in the observed porohyperelastic properties between arterial regions [4].…”
Section: Introductionmentioning
confidence: 99%